Interpretation And Obedience : From Faithful Reading To Faithful Living - Brueggemann, Walter (Minneapolis : Fortress Press, 1991)
Drawing on specific texts that speak to cosmic hurt and personal possibility, Walter Brueggemann demonstrates the essential connection between faithful reading of the biblical text and faithful living in a world of banal, yet threatening values. He assesses the nature of obedience today in such areas as ministry, justice, the land, education, hospitality, and the contemporary imagination. - Publisher.
Third world of evangelical imagination -- Embarrassing footnote -- Legitimacy of sectarian hermeneutic : 2 Kings 18-19 -- Transformative potential of a public metaphor : Isaiah 37:21-29 -- Case for an alternative reading -- Canonization and contextualization -- Commandments and liberated, liberating bonding -- Transformative agenda of the pastoral office -- Monopoly and marginality in imagination -- God's faithful plan : a context for caring citizenship -- Land : fertility and justice -- Land and our urban appetites -- Welcoming the stranger -- Cosmic hurt/personal possibility : Jer. 4:23-28; Isa. 45:18-22; Luke 6:21-31.
Includes bibliographical references and index.
Keywords: Bible. -- Hermeneutics; Bible. -- Criticism, interpretation, etc; Ethics in the Bible; Obedience -- Biblical teaching; Christian ethics -- Lutheran authors; Criticism, interpretation, etc